(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the theoretical and practical aspects of creating a digital pedagogical environment based on mobile technologies in basketball education. It is emphasized that the rapid development of information and communication technologies requires new pedagogical approaches in the educational process. On this basis, mobile applications are considered as an important innovative tool in basketball education. The study highlights the possibilities of organizing the educational process within the framework of the mobile learning concept and the methodological foundations of its optimization. The pedagogical capabilities of the PJT (Professional Basketball) mobile application created by the author are also analyzed. The results show that mobile technologies are effective in increasing the efficiency of basketball education, increasing player motivation, and monitoring technical and tactical development.